Misleading Rare Case of Idiopathic Hypertrophic Pachymeningitis - Ahmad Rezaee Azandaryani; Amir Mohammad Salehi (Case Reports in Medicine)
Idiopathic hypertrophic pachymeningitis (IHP) is a rare disease with diffuse thickening of the dura mater that has no specific clinical symptoms and manifestations and it causes neurosurgeons to misdiagnose. A 4-year-old girl presented at the emergency room of our hospital with speech difficulty and severe headache. Head computed tomography scans (CT scan) on admission revealed a large fluid collection over the right temporoparietal region with mass effect, and the neurosurgeon drained it with the initial diagnosis of subdural hematoma. However, the postoperative CT scan demonstrated the failure of surgical drainage; therefore, magnetic resonance imaging (MRI) was requested for the patient. MRI identified diffuse nodular dural thickening with internal septations and different internal hemorrhagic stages on the right side with no evidence of brain parenchymal involvement and according to the serology and autoimmune screening tests, and IHP was diagnosed for the patient. The patient underwent craniotomy. There was an immediate improvement of neurologic symptoms. The patient had good clinical and radiologic outcome at 3 -months follow-up. IHP should be part of the differential diagnosis of some cases of noncommunicating hydrocephalus; however, the rarity of the disease and the absence of specific clinical symptoms make the diagnosis difficult.